2007
DOI: 10.1596/1813-9450-4102
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Cash Transfers And Female Schooling : The Impact Of The Female School Stipend Program On Public School Enrollments In Punjab, Pakistan

Abstract: Instead of mean-tested Conditional Cash Transfer (CCT) programs, some countries have implemented gender-targeted CCTs to explicitly address intra-household disparities in human capital investments. This study focuses on addressing the direct impact of a female school stipend program in Punjab, Pakistan -Did the intervention increase female enrollment in public schools? To address this question, we draw upon data from the provincial school censuses 2003 and 2005. We estimate the net growth in female enrollments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…These assessments have been corroborated by subsequent evaluations of similar interventions in Brazil, Honduras, Colombia, Cambodia, Nicaragua, Turkey, Pakistan, Malawi, and El Salvador. For the most part, their findings are consistent with the results of the Oportunidades program regarding positive impacts on the use of educational and health services and short-term consumption (Olinto et al, 2003;Glewwe and Olinto, 2004;Attanasio and Mesnard, 2005;Attanasio et al, 2005a and2005b;Filmer and Schady, 2006;Maluccio and Flores, 2005;Ahmed et al, 2007;Chaudhury and Parajuli, 2008;Baird et al, 2009). 4 In addition to positive effects on school attendance and enrollment, some evaluations also suggest that grade progression improves with CCTs.…”
Section: Related Literaturesupporting
confidence: 67%
See 2 more Smart Citations
“…These assessments have been corroborated by subsequent evaluations of similar interventions in Brazil, Honduras, Colombia, Cambodia, Nicaragua, Turkey, Pakistan, Malawi, and El Salvador. For the most part, their findings are consistent with the results of the Oportunidades program regarding positive impacts on the use of educational and health services and short-term consumption (Olinto et al, 2003;Glewwe and Olinto, 2004;Attanasio and Mesnard, 2005;Attanasio et al, 2005a and2005b;Filmer and Schady, 2006;Maluccio and Flores, 2005;Ahmed et al, 2007;Chaudhury and Parajuli, 2008;Baird et al, 2009). 4 In addition to positive effects on school attendance and enrollment, some evaluations also suggest that grade progression improves with CCTs.…”
Section: Related Literaturesupporting
confidence: 67%
“…al., 2009 (Filmer and Schady, 2006). A most directly related to this analysis, the short-term impact evaluation of the FSSP in Pakistan -the program analyzed in this paper -shows an increase in the enrollment of girls of about nine percentage points between 2003(Chaudhury and Parajuli, 2008. Although the impacts of these studies differ by magnitude, and the empirircal approaches vary, results appear to be consistent across programs and implementation contexts.…”
Section: Related Literaturementioning
confidence: 69%
See 1 more Smart Citation
“…Other research conducted both in other developing countries (Schultz, 2004;De Janvry et al, 2006;Heinrich, 2007;Chaudhury and Parajuli, 2008;De Brauw and Hoddinott, 2011;Barrera-Osorio et al, 2011;) and even in rural China (Mo et al, 2013) has shown that CCTs can be effective in boosting school enrollment and/or decreasing school dropout. So why did the CCT not have greater impact on the students in our sample?…”
Section: Resultsmentioning
confidence: 99%
“…As of 2008, more than 20 lowand middle-income countries had such education-targeted CCT programs in place (Fiszbein et al, 2009). These CCT programs have been shown to raise education matriculation and attendance in many countries, such as in Colombia (Attanasio et al, 2010;Barrera-Osorio et al, 2011), Pakistan (Chaudhury and Parajuli, 2008), Mexico (Schultz, 2004;De Janvry et al, 2006;De Brauw and Hoddinott, 2011), and Brazil (Heinrich, 2007;Glewwe and Kassouf, 2012). A subset of these studies in Colombia and Mexico found impacts of CCT programs on matriculation and attendance at the high school level in particular (Heinrich, 2007;Attanasio et al, 2010;Barrera-Osorio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%